Atividade in vitro da fosfolipases A2 e da fração peptídica extraídas do veneno de Crotalus durissus terrificus sobre formas amastogotas e promastigotas de Leishmania (L) infantum chagasi - Barros, Gustavo Adolfo Calsolari de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
American visceral leishmaniasis is caused by the intracellular parasite Leishmania ( L ) infantum chagasi , and transmitted by sand fly Lutzomyia longipalpis. Treatment is based on classical chemotherapeutics with significant side effects and the search for new drugs is the greatest global challenge. Thus , this in vitro study aimed to evaluate the anti - leishmanicidal effect of Crotalus durissus terrificus venom’s fractions on promastigotes and amastigotes of Leishmania (L) infantum chagasi. The whole venom were purified two fractions called respectively phospholipase A2 (PLA2) and peptide. Furthermore, promastigotes and macrophage infected per amastigotes were exposed to serial dilutions of the peptide fraction and PLA2 at intervals varying between 1.5625 μg/mL and 200 μg/mL. Both showed activity against promastigotes and varies according to the tested doses and the time of incubation. The MTT assay (3-(4,5-Dimethyl-1,3- thiazol-2-yl)-3,5-diphenyl-2H-tetrazol-3-ium bromide) against promastigotes showed IC50 of 52.07 μg/mL to PLA2, and 16.98 μg/mL for peptide venom’s fraction. The MTT assay to evaluate the cytotoxicity in peritoneal macrophages showed an IC50 of 98 μg/mL for PLA2 and 16.98 μg/ml for peptide. In peritoneal macrophages infected by Leishmania (L) infantum chagasi amastigotes the PLA2 stimulated growth of parasites, at higher doses was able to control 23 % growth. The peptide fraction controlled 43 % of the intracellular parasite growth at a dose of 16.98 μg/mL, showing up this dose toxic to macrophages . Both fractions stimulated H2O2 production by macrophages but only PLA2 was able to stimulate NO production . The results encourage further studies to describe the metabolic pathways involved in cell death , as well as the prospect of molecules with antiparasitic activity present in the peptide fraction of Crotalus durissus terrificus

A leishmaniose visceral americana, causada pelo parasita intracelular Leishmania (L) infantum chagasi, é transmitida pela picada do mosquito Lutzomyia longipalpis. O tratamento é realizado à base de quimioterápicos clássicos, que desenvolvem importantes efeitos colaterais no hospedeiro. A prospecção de novas drogas é o grande desafio mundial do momento. Assim, este estudo realizado in vitro teve por objetivos avaliar o efeito anti-leishmania de frações do veneno de Crotalus durissus terrificus sobre as formas promastigotas e amastigotas de Leishmania (L) infantum chagasi. Do veneno total foram extraídas e purificadas duas frações denominadas respectivamente de fosfolipase A2 (PLA2) e peptídica. Além disso, formas promastigotas e macrófagos infectados por amastigotas foram expostos a uma diluição seriada de PLA2 e da fração peptídica em intervalos que variaram entre 1,5625 μg/mL e 200 μg/mL. Ambas demonstraram atividade contra as formas promastigotas de Leishmania (L.) infantum chagasi variando de acordo com as doses testadas e o tempo de incubação. O ensaio MTT (3- (4,5-dimetiltiazol-2yl)-2,5-difenil brometo de tetrazolina) das frações contra as formas promastigotas mostrou IC50 de 52,07 μg /mL para a PLA2, e uma IC50 de 16,98 μg/mL para a fração peptídica. O ensaio MTT para se avaliar a citotoxicidade nos macrófagos peritoneais mostrou uma IC50 de 98 μg/mL para PLA2 e uma IC50 16,98 μg/mL para a fração peptídica. Nos macrófagos peritoneais infectados pelas formas amastigotas de Leishmania (L) infantum chagasi a PLA2 estimulou o crescimento dos parasitas; em doses mais elevadas foi capaz de controlar em 23% o seu crescimento. A fração peptídica controlou 43% do crescimento do parasita intracelular na dose de 16,98 μg/mL., mostrando-se tóxica acima desta doe para os macrófagos. Ambas as frações estimularam a produção de H2O2 pelos macrófagos, mas apenas PLA2 foi capaz de estimular a produção ...
Keywords: Peptídeos; Serpente peçonhenta - Peçonha; Leishmaniose visceral; Medicina tropical; Kala-azar